Progressive Law and Environmental Refugee Protection: Reconstructing The Paradigm of Substantive Justice In Indonesia - Setyardi, Untung (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This research analyzes refugee protection in Indonesia from the perspective of progressive law, aiming to reconstruct a substantive justice paradigm in response to the limitations of legal-formalistic and positivistic approaches. The study is driven by the absence of comprehensive national legislation on refugee protection and Indonesia’s non-ratification of the 1951 Refugee Convention and its 1967 Protocol, which have resulted in legal uncertainty and the treatment of refugees primarily as immigration issues rather than as rights-bearing individuals. This problem is further exacerbated by the emerging phenomenon of environmental refugees displaced by climate change, environmental degradation, and ecological disasters, who remain largely unrecognized within existing legal frameworks despite facing serious threats to their lives and dignity. Using a normative-juridical method with conceptual and philosophical analysis, this research examines progressive law theory, constitutional values, Pancasila, and fundamental principles of international human rights law, particularly the principle of non-refoulement. The findings demonstrate that reliance on formal legality alone is insufficient to ensure meaningful protection for both conventional and environmental refugees, while progressive law offers a humanistic framework that prioritizes human dignity and substantive justice beyond written norms. The study concludes that refugee protection in Indonesia requires a paradigm shift toward a progressive law approach grounded in constitutional and humanitarian values to effectively safeguard refugees’ fundamental rights.